Menjelajahi Kesenjangan Sosial-Ekonomi dan Kebijakan Publik pada Masyarakat Suku Akit di Kepulauan Meranti - Siregar, Muhammad Ridho; Natalia, Kristina; Sinaga, Fitri Pilami, Martina Apriani; Aulia, Nola Rahma; Utami, Bunga Chintia (Bahasa Indonesia, 2024)
This research aims to identify the conditions of social and economic inequality experienced by the Akit people in the Meranti Islands and how the implementation of public policy towards the inequality faced by the Akit Tribe as a Remote Indigenous Community (KAT). The location of this research was determined by purposive method, namely in Tenan Village, Tebing Tinggi Barat District, Meranti Islands Regency. The research method used is a qualitative method with in-depth interviews to key informants by purposive sampling. Data collection techniques were primary interviews and secondary data derived from data on the population of Tenan Village and the social service office of West Tebing Tinggi Sub-district, books and journals. Data analysis was processed using content analysis (research focus) linked to the findings of the literature study. The results show that the Akit community experiences social and economic inequality seen from four aspects, namely poverty levels, livelihoods, education, and access to health services. Meanwhile, the implementation of the KAT empowerment policy has not been well socialized.